Skin biopsy in the pediatric age group - Geeti Khullar; Chirag Desai (Wolters Kluwer Medknow Publications, 2022)
Skin biopsy has a crucial place in arriving at a definitive diagnosis in many pediatric dermatologic conditions. The need to perform a skin biopsy on a child may provoke apprehension in the parents/caregivers, which can be alleviated by establishing a good rapport with them. The details of the procedure, including benefits and risks involved, and the expected result should be communicated to the parents in an easy-to-understand language to have an informed decision. In this review, literature search was done across the PubMed database from January 1992 to January 2022 using the following keywords "skin biopsy in children," "skin biopsy in pediatric age group," "pediatric dermatopathology," "dermatologic surgery in children," "dermatologic surgery in pediatric age group," "pediatric dermatologic surgery," and "procedures in pediatric dermatology." Articles not written in the English language were excluded.